[Cu6I6] cluster lanthanide series-containing microporous catalytic material as well as preparation method and application thereof in catalysis of CO2 carboxylic acid cyclization

By catalyzing the carboxylic acid cyclization of CO2 and propargyl alcohol under normal temperature and pressure, the problem of cumbersome preparation of catalytic systems and limited application scope of substrates in the prior art is solved, and high efficiency is achieved , environmentally friendly CO2 fixation and conversion, with a yield of up to 99%, suitable for factory waste gas treatment.

CN119219673APending Publication Date: 2024-12-31LUOYANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324839.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing catalytic system has problems such as cumbersome preparation and limited application scope of expensive metal elements or substrates when catalyzing the carboxylic acid cyclization reaction between CO2 and propargyl alcohol, especially when it is difficult to achieve efficient catalysis at room temperature and pressure.

Method used

Using [Cu6I6] cluster lanthanide microporous catalytic material, it is prepared by sonication and solvothermal reaction, and it is used to catalyze the carboxylic acid cyclization reaction between CO2 and propargyl alcohol under normal temperature and pressure to obtain a high added value alkylene ring Carbonate fine chemical products.

Benefits of technology

It has achieved efficient catalytic carboxylic acid cyclization of CO2 and propargyl alcohol under normal temperature and pressure, with a yield of up to 99%, mild reaction conditions, good reproduction, simple separation, suitable for the fixation and conversion of factory waste gas, significantly improving the environment benefit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219673A_ABST
    Figure CN119219673A_ABST
Patent Text Reader

Abstract

The invention relates to a [Cu6I6] cluster lanthanide series-containing microporous catalytic material and a preparation method and application thereof in catalysis of CO2 carboxylic acid cyclization, the molecular formula of the catalytic material is [Eu2Cu6I6 (pyrc) 4 (DMF) 6], and the ligand pyrc is 4-pyrazole carboxylic acid; the crystal structure of the catalytic material belongs to a triclinic system, the space group is Pi, and the cell parameters are as follows: # imgabs0 # imgabs1 # alpha = 84.072 (4) degrees, beta = 88.384 (3) degrees, gamma = 87.343 (4) degrees and # imgabs2 #. The preparation method comprises the following steps: S1, adding 4-pyrazole carboxylic acid and Eu (NO3) 3.9 H2O into DMF (Dimethyl Formamide), and performing ultrasonic treatment to form a solution A; s2, adding CuI into DMF, and performing ultrasonic treatment to form a turbid liquid B; and S3, mixing A and B, carrying out ultrasonic treatment, transferring into a pressure-resistant bottle, heating to 125 DEG C at a speed of 10 DEG C / min, carrying out heat preservation for 24 hours, carrying out solvothermal reaction, and cooling to room temperature at a speed of 5 DEG C / min to obtain the crystal. The [Cu6I6] cluster lanthanide series microporous material catalyzes CO2 and propargyl alcohol to perform carboxylic acid cyclization at normal temperature and normal pressure to obtain a target product alkylene cyclic carbonate product. The [Cu6I6] cluster lanthanide series microporous catalytic material is used for catalyzing CO2 and propargyl alcohol to carry out carboxylic acid cyclization reaction at normal temperature and normal pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of microporous material preparation and catalysts thereof, in particular to a lanthanide microporous catalytic material containing a [Cu6I6] cluster and a preparation method thereof and application in catalyzing CO2 carboxylic acid cyclization. Background Art

[0002] Large-scale emission of greenhouse gas CO2 in industrial waste gas is the main cause of global warming. Fixing the emitted CO2 and catalytically converting it into other substances is an effective way to reduce the CO2 content in the atmosphere. Fixing CO2 and converting it into high-value-added chemicals through green and environmentally friendly reaction processes has become a hot research frontier.

[0003] CO2 is an abundant, cheap and non-toxic C1 resource, but due to its high thermodynamic stability and kinetic inertness, CO2 shows low reactivity during the conversion process. Therefore, it is extremely important to find an efficient catalytic system and use green and environmentally friendly reaction processes under environmental conditions to achieve efficient catalytic conversion of CO2.

[0004] Patent US2024198320A1 reports the use of ZIF-8 as a microporous heterogeneous catalytic material to catalyze the reaction of CO2 and epoxy compounds to produce cyclic carbonate lactone compounds. However, in this reaction, the yield of the target product fluctuates greatly, ranging from 20% to 99%, indicating that the applicable reaction substrates are limited.

[0005] Patent CN104130236A discloses that the ligand obtained by the reaction of glycine and salicylaldehyde is reacted with some transition metal ions to obtain a series of heterogeneous catalytic materials, which achieves good catalysis of CO2 and epoxy compounds to produce cyclic carbonate lactone compounds under the reaction temperature of 80°C. It should be pointed out that the invention still does not solve the catalytic conversion reaction of CO2 under ambient temperature conditions.

[0006] Patent CN109081817A discloses a CuI and ionic liquid combination that catalyzes CO2 and propargyl alcohol for carboxylic acid cyclization. Although the reaction yield is high, the reaction system cannot be reused, and the reaction temperature is higher than room temperature, requiring a reaction temperature of about 30°C.

[0007] Literature (Cui, HY, et al, Chem. Eng. J., 2023, 451, 138764) and (Yang, YY, et al, ACS Catal. 2024, 14, 10344-10354) reported that the use of microporous metal organic framework materials can catalyze the carboxylic acid cyclization reaction of CO2 and propargyl alcohol at room temperature, with high reaction yield, and the catalyst can be reused, achieving green reaction conditions at room temperature and pressure. However, there are disadvantages such as the need to add organic solvents for the reaction and the cumbersome catalyst preparation steps.

[0008] Although a variety of catalytic systems have been reported to catalyze the carboxylic acid cyclization reaction of CO2 and terminal propargyl alcohol to prepare high value-added alkylene cyclic carbonate fine chemical products, this product is an important organic synthesis intermediate, can be used as a special organic solvent, and has very high commercial value in active drugs, pesticides and industry. However, the existing catalytic systems still have disadvantages such as cumbersome catalyst preparation, or the need for expensive metal elements, or limited substrate applicability. Based on the above-mentioned reaction condition limitations, it is urgent to find a green and environmentally friendly catalytic system that can catalyze the carboxylic acid cyclization reaction of CO2 and propargyl alcohol at room temperature and pressure. Summary of the invention

[0009] The present invention aims to provide a lanthanum microporous catalytic material containing [Cu6I6] clusters, a preparation method thereof and an application in catalyzing CO2 carboxylic acid cyclization, and utilizes the [Cu6I6] cluster lanthanum microporous catalytic material to catalyze the carboxylic acid cyclization reaction of CO2 and propargyl alcohol at room temperature and pressure.

[0010] In order to solve the above technical problems, the specific scheme adopted by the present invention is a lanthanide microporous catalytic material containing [Cu6I6] cluster: the molecular formula of the catalytic material is [Eu2Cu6I6(pyrc)4(DMF)6], wherein the ligand pyrc is 4-pyrazolecarboxylic acid; the crystal structure of the catalytic material belongs to the triclinic system, the space group is Pī, and its unit cell parameters are: α=84.072(4)°, β=88.384(3)°, γ=87.343(4)°, In its asymmetric unit cell, there are 7 Cu(I) ions, 1 Eu 3+ ions, 6 iodide ions, 3 pyrc ligand molecules and 3 DMF molecules.

[0011] The preparation method of the above-mentioned lanthanide microporous catalytic material containing [Cu6I6] clusters comprises the following steps:

[0012] S1: 4-pyrazolecarboxylic acid and Eu(NO3)3·9H2O were added to DMF solvent and subjected to ultrasonic treatment to form solution A;

[0013] S2: Take CuI and add it to DMF solvent, and perform ultrasonic treatment to form suspension B;

[0014] S3: Solution A and suspension B are mixed, and after ultrasonic treatment, they are transferred into a pressure bottle, and the temperature is raised to 120-125°C at a rate of 9.8-10.2°C / min and kept at this temperature for 20-26 hours for solvothermal reaction, and then cooled to room temperature at a rate of 4.8-5.2°C / min. The purple-red crystals obtained are the lanthanide microporous catalytic materials containing [Cu6I6] clusters.

[0015] As another optimized solution for the preparation method of the above-mentioned [Cu6I6] cluster-containing lanthanide microporous catalytic material: in the step S1, the molar ratio of 4-pyrazolecarboxylic acid and Eu(NO3)3·9H2O is 4 to 5:1.

[0016] As another optimization scheme for the preparation method of the above-mentioned [Cu6I6] cluster-containing lanthanide microporous catalytic material: in the step S3, the volume of the mixture of solution A and suspension B is 40-50% of the total volume of the pressure bottle, and the temperature is raised to 125°C and then kept warm for reaction for 24 hours.

[0017] As an application of the above-mentioned lanthanum microporous catalytic material containing [Cu6I6] clusters to efficiently catalyze the carboxylic acid cyclization of CO2 at room temperature and pressure: the lanthanum microporous catalytic material containing [Cu6I6] clusters catalyzes the carboxylic acid cyclization of CO2 and propargyl alcohol at room temperature and pressure to obtain alkylene cyclic carbonate fine chemical products.

[0018] As another optimization scheme for the application of the above-mentioned lanthanum microporous catalytic material containing [Cu6I6] clusters: using the lanthanum microporous catalytic material containing [Cu6I6] clusters as a heterogeneous catalyst, adding 1,8-diazabicyclo[5.4.0]undec-7-ene and propargyl alcohol, introducing CO2 gas for stirring reaction, adding ethyl acetate after the reaction, filtering and recovering the lanthanum microporous catalytic material containing [Cu6I6] clusters, and after vacuum rotary evaporation of the filtrate, using a mixed solution of petroleum ether and ethyl acetate at 60°C to 90°C as the mobile phase for column chromatography separation to obtain the target product, alkylene cyclic carbonate product.

[0019] As another optimization scheme for the application of the above-mentioned [Cu6I6] cluster-containing lanthanide microporous catalytic material: the propargyl alcohol is one or more of 2-methyl-3-butyn-2-ol, 3-methyl-1-pentyn-3-ol, 3-ethyl-1-pentyn-3-ol and 3,4-dimethyl-1-pentyn-3-ol.

[0020] As another optimization scheme for the application of the above-mentioned lanthanum microporous catalytic material containing [Cu6I6] clusters: the amount of lanthanum microporous material containing [Cu6I6] clusters is 0.7 to 1 mol% of the amount of propargyl alcohol.

[0021] As another optimization scheme for the application of the above-mentioned [Cu6I6] cluster-containing lanthanide microporous catalytic material: the amount of 1,8-diazabicyclo[5.4.0]undec-7-ene is 45 to 50 mol% of the amount of propargyl alcohol.

[0022] As another optimization scheme for the application of the above-mentioned [Cu6I6] cluster-containing lanthanide microporous catalytic material: the pressure of the introduced CO2 gas is 0.8 to 1.2 atm.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The [Cu6I6] cluster lanthanum microporous catalytic material of the present invention has a simple preparation method, and the [Cu6I6] cluster lanthanum microporous catalytic material can be used as a heterogeneous catalyst to efficiently catalyze CO2 and propargyl alcohol for carboxylic acid cyclization to obtain alkylene cyclic carbonate fine chemical products with high added value. It has the characteristics of mild reaction conditions, no need for high temperature and high pressure, good reaction reproducibility, simple reaction separation, significant catalytic effect, and a yield of the target reaction product of up to 99%. It is suitable for the fixation and conversion of CO2 in factory exhaust gas, and the environmental benefits are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A schematic diagram of the single crystal structure of the [Cu6I6] cluster lanthanide microporous catalytic material prepared in an embodiment of the present invention;

[0026] Figure 2 In situ preparation of [Cu6I6] cluster lanthanide microporous catalytic material for catalyzing CO2 and propargyl alcohol for carboxylic acid cyclization reaction 1 H-NMR mechanism diagram;

[0027] Figure 3 The powder diffraction pattern of the lanthanide microporous catalytic material containing [Cu6I6] cluster prepared in the embodiment of the present invention (including the powder diffraction pattern of single crystal simulation, the powder diffraction pattern of experimental measurement, and the powder diffraction pattern after 4 cycles of catalytic reaction). DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. Parts of the present invention that are not described in detail in the following embodiments, such as thin layer chromatography tracking reaction, 1 H-NMR in-situ nuclear magnetic detection technology and column chromatography, etc., should be prior arts that are immediately known or should be known to those skilled in the art.

[0029] Example 1

[0030] A lanthanide microporous catalytic material containing [Cu6I6] clusters, a preparation method thereof, and an application thereof in catalyzing CO2 carboxylic acid cyclization, comprising the following steps:

[0031] (I) Preparation of lanthanide microporous catalytic materials containing [Cu6I6] clusters

[0032] Weigh 134.4 mg 1.2 mmol 4-pyrazolecarboxylic acid and 134.2 mg 0.3 mmol Eu(NO3)3·6H2O, add them into a vial containing 6 mL DMF, and disperse them ultrasonically for 15 min to form solution A; add 57.1 mg 0.3 mmol CuI into a vial containing 4 mL DMF, and disperse them ultrasonically for 15 min to form suspension B; then, mix solution A and suspension B, and after 15 min of ultrasonication, transfer them into a 25 mL pressure bottle for solvothermal reaction, heat to 120°C at a rate of 10°C / min, keep the reaction at this temperature for 24 h, and then cool to room temperature at a cooling rate of 5°C / h to obtain purple-red crystals.

[0033] The purple-red crystal is the [Cu6I6] cluster-containing lanthanide microporous catalytic material in this embodiment, and its molecular formula is [Eu2Cu6I6(pyrc)4(DMF)6]. Based on Eu, its crystal yield is 55%. Crystal structure analysis shows that the unit cell parameters are: α=84.072(4)°, β=88.384(3)°, γ=87.343(4)°, In its asymmetric unit cell, there are 7 Cu(I) ions, 1 Eu ion, 6 iodine ions, 3 pyrc ligand molecules, and 3 DMF molecules. Its crystal structure is as follows: Figure 1 shown.

[0034] (II) Application of lanthanide microporous catalytic materials containing [Cu6I6] clusters to prepare alkylene cyclic carbonate fine chemical products

[0035] Weigh 32mg 0.01mmol of lanthanum microporous catalytic material containing [Cu6I6] cluster, 84mg 1mmol of 2-methyl-3-butyn-2-ol and 76mg 0.05mmol DBU into a 10ml three-necked flask, introduce CO2 gas with a pressure of 1atm into the three-necked flask, stir and react at a stirring speed of 30r / min at room temperature and pressure for 1h, and track the reaction process with thin layer chromatography. When the reaction is complete, add 50mL of ethyl acetate and stir for 10min, filter the obtained mixture, remove the solid catalyst, and evaporate the obtained filtrate under reduced pressure to obtain a crude product. The crude product is separated by column chromatography, and the mobile phase is a volume ratio of petroleum ether to ethyl acetate of 6:1, and a pure alkylene cyclic carbonate fine chemical product is separated, which is named 4,4-dimethyl-5-methylene-1,3-dioxolane-2-one, with a mass of 126.8mg and a yield of>99%. The product is analyzed by nuclear magnetic resonance, and its nuclear magnetic data is: 1H-NMR (CDCl3): 4.76 (d, J = 4.0 Hz, 1H), 4.30 (d, J = 4.0 Hz, 1H), 1.61 (s, 6H).

[0036] In order to further understand the reaction mechanism of the present embodiment, 1 H-NMR in-situ nuclear magnetic detection technology was used to detect the nuclear magnetic signals between propargyl alcohol 2-methyl-3-butyn-2-ol and the lanthanide microporous catalytic material containing [Cu6I6] clusters and DBU. Figure 2 As shown in the figure, when DBU or [Cu6I6] cluster lanthanum microporous catalytic material is added to 2-methyl-3-butyn-2-ol, the hydroxyl proton signal intensity at δ=5.28 becomes weaker compared with the original NMR spectrum of propargyl alcohol, which indicates that [Cu6I6] cluster lanthanum microporous catalytic material or DBU can activate the hydroxyl proton in propargyl alcohol alone. When DBU and [Cu6I6] cluster lanthanum microporous catalytic material are added to propargyl alcohol at the same time, the hydroxyl proton signal almost disappears, indicating that DBU and [Cu6I6] cluster lanthanum microporous catalytic material have a synergistic effect on propargyl alcohol. At the same time, after adding DBU and lanthanum microporous catalytic materials containing [Cu6I6] clusters, the H proton signal of the terminal alkynyl group in propargyl alcohol at δ=3.16 changed significantly, which shows that the lanthanum microporous catalytic materials containing [Cu6I6] clusters can effectively activate the carbon-carbon triple bond, promote the formation of active intermediates between propargyl alcohol and CO2, and thus complete the carboxylic acid cyclization reaction between CO2 and propargyl alcohol.

[0037] The solid catalyst obtained by filtration in the first step was washed with ethyl acetate, dried in vacuum and reused for at least 4 catalytic cycles. The solid catalyst was subjected to powder diffraction tests before and after use and compared with the powder pattern of the single crystal structure simulation. The results are as follows: Figure 3 shown.

[0038] Example 2

[0039] (I) Preparation of lanthanide microporous catalytic materials containing [Cu6I6] clusters

[0040] 134.3 mg (1.3 mmol) of 4-pyrazolecarboxylic acid and 134.6 mg (0.3 mmol) of Eu(NO3)3·6H2O were weighed and added to a vial containing 6 mL of DMF. After ultrasonic dispersion for 15 min, solution A was formed. 57.3 mg (0.3 mmol) of CuI was added to a vial containing 4 mL of DMF. After ultrasonic dispersion for 15 min, suspension B was formed. Then, solution A and suspension B were mixed, ultrasonicated for 15 min, and then transferred to a 25 mL pressure bottle for solvothermal reaction. The temperature was raised to 122°C at a rate of 10°C / min and kept at this temperature for 25 h. The temperature was then cooled to room temperature at a cooling rate of 5°C / h to obtain purple-red crystals.

[0041] The purple-red crystal is the [Cu6I6] cluster-containing lanthanide microporous catalytic material in this embodiment, and its molecular formula is [Eu2Cu6I6(pyrc)4(DMF)6]. Based on Eu, its crystal yield is 60%, and its crystal structure is as follows: Figure 1 shown.

[0042] (II) Application of lanthanide microporous catalytic materials containing [Cu6I6] clusters to prepare alkylene cyclic carbonate fine chemical products

[0043] 33.2mg 0.01mmol of lanthanide microporous catalytic material containing [Cu6I6] cluster, 85.3mg 1mmol of 2-methyl-3-butyn-2-ol and 80.3mg 0.52mmol DBU were weighed and added into a 10ml three-necked flask, CO2 gas with a pressure of 1atm was introduced into the three-necked flask, and stirred and reacted for 1h at a stirring speed of 30r / min at room temperature and pressure, and the reaction process was tracked by thin layer chromatography. When the reaction was complete, 50mL of ethyl acetate was added and stirred for 10min, the obtained mixture was filtered, the solid catalyst was removed, and the obtained filtrate was evaporated under reduced pressure to obtain a crude product. The crude product was separated by column chromatography, and a mobile phase of petroleum ether and ethyl acetate with a volume ratio of 3:1 was used to separate the pure alkylene cyclic carbonate fine chemical product, which was named 4,4-dimethyl-5-methylene-1,3-dioxolane-2-one, with a mass of 126.7mg and a yield of>99%.

[0044] Example 3

[0045] (I) Preparation of lanthanide microporous catalytic materials containing [Cu6I6] clusters

[0046] Weigh 146.6 mg (1.2 mmol) of 4-pyrazolecarboxylic acid and 134.6 mg (0.3 mmol) of Eu(NO3)3·6H2O, add them into a vial containing 6 mL of DMF, and disperse them ultrasonically for 15 min to form a solution A; add 57.4 mg (0.3 mmol) of CuI into a vial containing 4 mL of DMF, and disperse them ultrasonically for 15 min to form a suspension B; then, mix solution A and suspension B, and after 15 min of ultrasonic dispersion, transfer them into a 25 mL pressure bottle for solvothermal reaction, heat to 125°C at a rate of 10°C / min, keep the reaction at this temperature for 24 h, and then cool to room temperature at a cooling rate of 5°C / h to obtain purple-red crystals.

[0047] The purple-red crystal is the [Cu6I6] cluster-containing lanthanide microporous catalytic material in this embodiment, and its molecular formula is [Eu2Cu6I6(pyrc)4(DMF)6]. Based on Eu, its crystal yield is 50%, and its crystal structure is as follows: Figure 1 shown.

[0048] (II) Application of lanthanide microporous catalytic materials containing [Cu6I6] clusters to prepare alkylene cyclic carbonate fine chemical products

[0049] Weigh 33.1mg 0.01mmol of lanthanum microporous catalytic material containing [Cu6I6] cluster, 85.1mg 1mmol of 2-methyl-3-butyn-2-ol and 69.7mg 0.45mmol DBU into a 10ml three-necked flask, introduce CO2 gas with a pressure of 1atm into the three-necked flask, stir and react at a stirring speed of 30r / min at room temperature and pressure for 1h, and track the reaction process with thin layer chromatography. When the reaction is complete, add 50mL of ethyl acetate and stir for 10min, filter the obtained mixture, remove the solid catalyst, and evaporate the obtained filtrate under reduced pressure to obtain a crude product. The crude product is separated by column chromatography, and the mobile phase is a volume ratio of petroleum ether to ethyl acetate of 6:1, and a pure alkylene cyclic carbonate fine chemical product is separated, which is named 4,4-dimethyl-5-methylene-1,3-dioxolane-2-one, with a mass of 125.5mg and a yield of 98%.

[0050] Example 4

[0051] (I) Preparation of lanthanide microporous catalytic materials containing [Cu6I6] clusters

[0052] Weigh 156.8 mg (1.4 mmol) of 4-pyrazolecarboxylic acid and 134.6 mg (0.3 mmol) of Eu(NO3)3·6H2O, add them into a vial containing 6 mL of DMF, and disperse them ultrasonically for 15 min to form a solution A; add 57.3 mg (0.3 mmol) of CuI into a vial containing 4 mL of DMF, and disperse them ultrasonically for 15 min to form a suspension B; then, mix solution A and suspension B, and after 15 min of ultrasonic dispersion, transfer them into a 25 mL pressure bottle for solvothermal reaction, heat to 120°C at a rate of 10°C / min, keep the reaction at this temperature for 24 h, and then cool to room temperature at a cooling rate of 5°C / h to obtain purple-red crystals.

[0053] The purple-red crystal is the [Cu6I6] cluster-containing lanthanide microporous catalytic material in this embodiment, and its molecular formula is [Eu2Cu6I6(pyrc)4(DMF)6]. Based on Eu, its crystal yield is 52%, and its crystal structure is as follows: Figure 1 shown.

[0054] (II) Application of lanthanide microporous catalytic materials containing [Cu6I6] clusters to prepare alkylene cyclic carbonate fine chemical products

[0055] 33.2mg 0.01mmol of lanthanide microporous catalytic material containing [Cu6I6] cluster, 98.3mg 1mmol of 3-methyl-1-pentyn-3-ol and 76.7mg 0.5mmol DBU were added to a 10ml three-necked flask, CO2 gas with a pressure of 1atm was introduced into the three-necked flask, and the mixture was stirred and reacted at a stirring speed of 30r / min at room temperature and pressure for 1h, and the reaction process was tracked by thin layer chromatography. When the reaction was complete, 50mL of ethyl acetate was added and stirred for 10min, the obtained mixture was filtered, the solid catalyst was removed, and the obtained filtrate was evaporated under reduced pressure to obtain a crude product. The crude product was separated by column chromatography, and the mobile phase was a volume ratio of petroleum ether to ethyl acetate of 6:1, and a pure alkylene cyclic carbonate fine chemical product was separated, which was named 4-ethyl-4methyl-5-methylene-1,3-dioxolane-2-one, with a mass of 141.9mg and a yield of>99%. The product has been analyzed by NMR, and its NMR data are: 1 H-NMR (CDCl3): 4.81 (t, J = 4.0 Hz, 1H), 4.27 (d, J = 4.0 Hz, 1H), 1.91 (m, 1H), 1.58 (s, 3H), 0.96 (m, 3H).

[0056] Example 5

[0057] (I) Preparation of lanthanide microporous catalytic materials containing [Cu6I6] clusters

[0058] Weigh 168.3 mg (1.5 mmol) of 4-pyrazolecarboxylic acid and 134.4 mg (0.3 mmol) of Eu(NO3)3·6H2O, add them into a vial containing 6 mL of DMF, and disperse them ultrasonically for 15 min to form a solution A; add 57.2 mg (0.3 mmol) of CuI into a vial containing 4 mL of DMF, and disperse them ultrasonically for 15 min to form a suspension B; then, mix solution A and suspension B, and after 15 min of ultrasonic dispersion, transfer them into a 25 mL pressure bottle for solvothermal reaction, heat to 120°C at a rate of 10°C / min, keep the reaction at this temperature for 24 h, and then cool to room temperature at a rate of 5°C / h to obtain purple-red crystals.

[0059] The purple-red crystal is the [Cu6I6] cluster-containing lanthanide microporous catalytic material in this embodiment, and its molecular formula is [Eu2Cu6I6(pyrc)4(DMF)6]. Based on Eu, its crystal yield is 52%, and its crystal structure is as follows: Figure 1 shown.

[0060] (II) Application of lanthanide microporous catalytic materials containing [Cu6I6] clusters to prepare alkylene cyclic carbonate fine chemical products

[0061] 33.3mg 0.01mmol of lanthanide microporous catalytic material containing [Cu6I6] cluster, 112.4mg 1mmol of 3-methyl-1-pentyn-3-ol and 76.6mg 0.5mmol DBU were added to a 10ml three-necked flask, CO2 gas with a pressure of 1atm was introduced into the three-necked flask, and the mixture was stirred and reacted at a stirring speed of 30r / min at room temperature and pressure for 1h, and the reaction process was tracked by thin layer chromatography. When the reaction was complete, 50mL of ethyl acetate was added and stirred for 10min, the obtained mixture was filtered, the solid catalyst was removed, and the obtained filtrate was evaporated under reduced pressure to obtain a crude product. The crude product was separated by column chromatography, and the mobile phase was a volume ratio of petroleum ether to ethyl acetate of 6:1, and a pure alkylene cyclic carbonate fine chemical product was separated, which was named 4,4-ethyl-5-methylene-1,3-dioxolane-2-one, with a mass of 151.6mg and a yield of>99%. The product has been analyzed by NMR, and its NMR data are: 1 H-NMR (CDCl3): 4.86 (d, J = 4.0 Hz, 1H), 4.21 (d, J = 4.0 Hz, 1H), 2.02-1.86 (m, 2H), 1.70 (m, 2H), 0.98 (m, 6H).

[0062] Example 6

[0063] (I) Preparation of lanthanide microporous catalytic materials containing [Cu6I6] clusters

[0064] Weigh 168.2 mg 1.5 mmol 4-pyrazolecarboxylic acid and 134.6 mg 0.3 mmol Eu(NO3)3·6H2O, add them into a vial containing 6 mL DMF, and disperse them ultrasonically for 15 min to form solution A; add 57.5 mg 0.3 mmol CuI into a vial containing 4 mL DMF, and disperse them ultrasonically for 15 min to form suspension B; then, mix solution A and suspension B, and after 15 min of ultrasonication, transfer them into a 25 mL pressure bottle for solvothermal reaction, heat to 123 °C at a rate of 10 °C / min, keep the reaction at this temperature for 26 h, and then cool to room temperature at a cooling rate of 5 °C / h to obtain purple-red crystals.

[0065] The purple-red crystal is the [Cu6I6] cluster-containing lanthanide microporous catalytic material in this embodiment, and its molecular formula is [Eu2Cu6I6(pyrc)4(DMF)6]. Based on Eu, its crystal yield is 55%, and its crystal structure is as follows: Figure 1 shown.

[0066] (II) Application of lanthanide microporous catalytic materials containing [Cu6I6] clusters to prepare alkylene cyclic carbonate fine chemical products

[0067] 33.4mg 0.01mmol of lanthanide microporous catalytic material containing [Cu6I6] cluster, 112.4mg 1mmol of 3,4-dimethyl-1-pentyn-3-ol and 76.8mg 0.5mmol DBU were added to a 10ml three-necked flask, CO2 gas with a pressure of 1atm was introduced into the three-necked flask, and the mixture was stirred and reacted at a stirring speed of 30r / min at room temperature and pressure for 1h, and the reaction process was tracked by thin layer chromatography. When the reaction was complete, 50mL of ethyl acetate was added and stirred for 10min, the obtained mixture was filtered, the solid catalyst was removed, and the obtained filtrate was evaporated under reduced pressure to obtain a crude product. The crude product was separated by column chromatography, and the mobile phase was a volume ratio of petroleum ether to ethyl acetate of 6:1, and a pure alkylene cyclic carbonate fine chemical product was separated, which was named 4-isopropyl-4-methyl-5-methylene-1,3-dioxolane-2-one, with a mass of 139.7mg and a yield of>99%. The product has been analyzed by NMR, and its NMR data are: 1 H-NMR (CDCl3): 4.80 (d, J=4.0Hz, 1H), 4.25 (d, J=4.0Hz, 1H), 1.93 (m, 2H), 1.55 (s, 3H), 1.05 (d, J=4Hz, 3H), 0.98 (d, J=7.8Hz, 3H).

[0068] In combination with the above-mentioned Examples 1-6, it can be seen that the preparation method of the [Cu6I6] cluster lanthanum microporous catalytic material used in the present invention is simple, does not require the participation of expensive metal elements, and uses the prepared [Cu6I6] cluster lanthanum microporous catalytic material as a heterogeneous catalyst to efficiently catalyze CO2 and propargyl alcohol for carboxylic acid cyclization to obtain alkylene cyclic carbonate fine chemical products at room temperature and pressure. The whole process has the advantages of mild reaction conditions, no need for high temperature and high pressure, good reaction reproducibility, simple reaction separation, significant catalytic effect, and a yield of the target reaction product of up to 99%.

Claims

1. A lanthanide microporous catalytic material containing [Cu6I6] clusters, characterized in that: The molecular formula of the catalytic material is [Eu2Cu6I6(pyrc)4(DMF)6], wherein the ligand pyrc is 4-pyrazolecarboxylic acid; the crystal structure of the catalytic material belongs to the triclinic system, the space group is Pī, and the unit cell parameters are: α=84.072(4)°, β=88.384(3)°, γ=87.343(4)°, In its asymmetric unit cell, there are 7 Cu(I) ions, 1 Eu 3+ ions, 6 iodide ions, 3 pyrc ligand molecules and 3 DMF molecules.

2. The method for preparing the [Cu6I6] cluster-containing lanthanide microporous catalytic material according to claim 1, characterized in that: The steps include: S1: 4-pyrazolecarboxylic acid and Eu(NO3)3·9H2O were added to DMF solvent and subjected to ultrasonic treatment to form solution A; S2: Take CuI and add it to DMF solvent, and perform ultrasonic treatment to form suspension B; S3: Solution A and suspension B are mixed, and after ultrasonic treatment, they are transferred into a pressure bottle, and the temperature is raised to 120-125°C at a rate of 9.8-10.2°C / min and kept at this temperature for 20-26 hours for solvothermal reaction, and then cooled to room temperature at a rate of 4.8-5.2°C / min. The purple-red crystals obtained are the lanthanide microporous catalytic materials containing [Cu6I6] clusters.

3. The method for preparing the [Cu6I6] cluster-containing lanthanide microporous catalytic material according to claim 2, characterized in that: In the step S1, the molar ratio of 4-pyrazolecarboxylic acid to Eu(NO3)3·9H2O is 4 to 5:

1.

4. The method for preparing a lanthanide microporous catalytic material containing [Cu6I6] clusters as claimed in claim 3, characterized in that: In step S3, the volume of the mixture of solution A and suspension B is 40-50% of the total volume of the pressure bottle, and the mixture is heated to 125° C. and kept warm for 24 hours.

5. The use of the [Cu6I6] cluster-containing lanthanide microporous catalytic material as claimed in claim 1 for efficiently catalyzing CO2 carboxylic acid cyclization at room temperature and pressure, characterized in that: The lanthanide microporous catalytic material containing [Cu6I6] cluster catalyzes the carboxylic acid cyclization of CO2 and propargyl alcohol at room temperature and pressure to obtain alkylene cyclic carbonate fine chemical products.

6. The use of the [Cu6I6] cluster-containing lanthanide microporous catalytic material as claimed in claim 5, characterized in that: The lanthanum microporous catalytic material containing [Cu6I6] cluster is used as a heterogeneous catalyst, 1,8-diazabicyclo[5.4.0]undec-7-ene and propargyl alcohol are added, CO2 gas is introduced for stirring reaction, ethyl acetate is added after the reaction is completed, the lanthanum microporous catalytic material containing [Cu6I6] cluster is filtered and recovered, the filtrate is subjected to reduced pressure rotary evaporation, and a mixed solution of petroleum ether and ethyl acetate at 60°C to 90°C is used as a mobile phase for column chromatography separation to obtain the target product, alkylene cyclic carbonate product.

7. The use of the [Cu6I6] cluster-containing lanthanide microporous catalytic material as claimed in claim 6, characterized in that: The propargyl alcohol is one or more of 2-methyl-3-butyn-2-ol, 3-methyl-1-pentyn-3-ol, 3-ethyl-1-pentyn-3-ol and 3,4-dimethyl-1-pentyn-3-ol.

8. The use of the [Cu6I6] cluster-containing lanthanide microporous catalytic material as claimed in claim 6, characterized in that: The amount of the lanthanum microporous catalytic material containing [Cu6I6] cluster is 0.7 to 1 mol% of the amount of propargyl alcohol.

9. The use of the [Cu6I6] cluster-containing lanthanide microporous catalytic material as claimed in claim 6, characterized in that: The amount of 1,8-diazabicyclo[5.4.0]undec-7-ene is 45 to 50 mol% of the amount of propargyl alcohol.

10. The use of the [Cu6I6] cluster-containing lanthanide microporous catalytic material as claimed in claim 6, characterized in that: The pressure of the introduced CO2 gas is 0.8~1.2atm.